Patterns of Enrollment Churn in Medicaid Expansion, Subsequent Insurance Coverage, and Access to Care: A Longitudinal Study. (20th August 2020) - Goold, S.; Tipirneni, R.; Ayanian, J.; Beathard, E.; Chang, T.; Haggins, A.; Kieffer, E.; Kirch, M.; Kullgren, J.T.; Lee, S.; Lewallen, M.; Patel, M.; et al.
Abstract : Understand enrollment patterns in Medicaid expansion and how churn and disenrollment affect access to care. We conducted telephone surveys with a cohort of Medicaid expansion enrollees at 3 time points in 2016, 2017, and 2018 (N = 2, 608, RR = 89.4%). Surveys measured health, access to care, and insurance status. Respondents who had no HMP/Medicaid enrollment for > 3 consecutive months but re‐enrolled (according to state records) were categorized as "churned off/on"; those who had disenrolled from HMP/Medicaid for > 6 months were categorized as "off for > 6 months"; the remainder were categorized as "stayed on." We used Pearson chi‐square tests to compare groups and mixed models with year as a fixed effect to assess changes over time, incorporating weights adjusting for sample design and nonresponse. HMP beneficiaries with ≥ 12 months of HMP coverage in 2016. As of 2018, 74.2% stayed on HMP/Medicaid, 9.8% churned off/on, and 16.0% were off for > 6 months. Going off HMP/Medicaid for > 6 months was more likely for men than women (17.7% vs. 14.6%), those age 19‐34 and 35‐50 compared to 51‐64 (17.1%, 17.0%, and 13.3%), those who were married/partnered compared to those who were not (18.6% vs. 14.3%), those with compared to without a chronic condition (18.9% vs. 14.3%), and those without compared to with a mental health condition or substance use disorder (22.1% vs. 12.6%) (all, P  < .05). Employed respondents in 2017 or 2018 were more likely than those unemployed to have gone off HMP/Medicaid for > 6 months (21.7% vs. 5.2%, P  < .001)). Employed respondents (11.1% vs. 7.0% not employed), black respondents (14.7% vs. 7.1% white), men (11.7% vs. 7.9% women), those in the youngest age group (14.4% vs. 7.5% for 35‐50 and 5.7% 51‐64), and those not married/partnered (11.3% vs. 7.3% married/partnered) were all more likely to churn off/on (all, P  < .05). More than half (58.9%) of respondents who were off for > 6 months had a period of uninsurance in 2017 or 2018. Respondents who were off > 6 months were less likely than those who stayed on to report having a regular source of care (84.6% vs 93.9%), more likely to report forgone health care for financial reasons (17.0% vs. 3.2%) and more likely to report problems paying medical bills (32.6% vs. 17.5%). Those who churned off/on were also less likely than those who stayed on to report having a regular source of care (83.6% vs. 93.9%) more likely to report forgone health care for financial reasons (7.5% vs. 3.2%) and more likely to report problems paying medical bills (40.4% vs. 17.5%). In a longitudinal study of Medicaid expansion, approximately a quarter of enrollees had either churned off and on HMP/Medicaid or had extended disenrollment over a three‐year period. Those who had experienced churn or extended disenrollment were more likely to report forgone health care, not having a regular source of care, and problems paying medical bills. Many Medicaid enrollees who experience churn or disenrollment have difficulty maintaining health insurance and face financial obstacles to care. Michigan Department of Health and Human Services.